Aplicação de geotecnologias para caracterização da piscicultura na Bacia Hidrográfica do Rio Marreco - Morsoleto, Felipe Misael da Silva (2020)
In the Hydrographic basin of Rio Marreco / PR, it concentrates a productive chain of fish farming and a great intensification of tilapia farming. In this work, we aim at the knowledge of morphometry, monitoring the quality of effluent water and organic and inorganic elements released by fish farming, in excavated ponds, using geomorphological data (slope and altitude) and land use and occupation. Methodologically, the Terrain Analysis Using Digital Elevation Models (TauDEM) software was used based on the Digital Elevation Model (MDE) for Watershed Delimitation in the software QGIS v. 3.6.3. As a result, we obtained the form factor and circularity index considered low, 0.17 and 0.16, compactness index is 2.44, indicating the basin classified as elongated and with low risk of flooding. Altogether in this work, 1,457 production units (water depths) were identified in the entire study area, which represented an occupied area of 162.2 ha. There were the following findings when characterizing the sub-basins; Alto Marreco, the sub-basin with the largest production logistics, has its best-known productive means compared to Baixo Marreco, which still lacks a greater logistical contribution and because it is not yet fully integrated and does not have this network of relationships. ) and the Middle Marreco, which does not have fish farming as its main agricultural practice, but its use as an opportunity for inputs with other agricultural activities. The sub-basins showed a supply of nutrients and in order to reduce these nutrients, it is recommended to implement systems for decanting and / or reusing wastewater. For the environmental managers, the results of this study show how important it is to know the dynamics of the nutrients in the creations and the physical characteristics of the drainage basin, to determine the support capacity of the environment, so as not to allow licenses that promote impacts above the capacity of self-cleaning of water courses.